2021
DOI: 10.1177/15385744211051495
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Hospitalized COVID-19 Patients Treated in a Single Academic Center in Mexico: A Case Series Study

Abstract: Background The increasing prevalence of venous thromboembolism (VTE) among patients with coronavirus disease 2019 (COVID-19) is a matter of concern as it contributes significantly to patients' morbidity and mortality. Data regarding the optimal anticoagulation regimen for VTE prevention and treatment remain scarce. This study describes the characteristics, treatment, and outcomes of COVID-19 patients with VTE treated in a single academic center in Mexico. Methods We conducted a retrospective study of all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Ad hoc studies evaluating prospectively the temporal trend of DVT incidence in patients hospitalized for COVID-19 are lacking, and we can only extrapolate data by indirect comparison of studies that were carried out at different times of the pandemic. Pooled data from a metanalysis published by Zhang et al during the period March-November 2020 (first wave) showed a cumulative incidence of DVT of 7% in patients hospitalized for COVID-19 outside the ICU [16]; while, two recent studies pertaining to the second phases of the pandemic reported a cumulative incidence of DVT in the range of 1-3% in non-ICU patients, features similar to 4.2% incidence found in the second wave in our study [10,[17][18][19].…”
Section: Discussionsupporting
confidence: 85%
“…Ad hoc studies evaluating prospectively the temporal trend of DVT incidence in patients hospitalized for COVID-19 are lacking, and we can only extrapolate data by indirect comparison of studies that were carried out at different times of the pandemic. Pooled data from a metanalysis published by Zhang et al during the period March-November 2020 (first wave) showed a cumulative incidence of DVT of 7% in patients hospitalized for COVID-19 outside the ICU [16]; while, two recent studies pertaining to the second phases of the pandemic reported a cumulative incidence of DVT in the range of 1-3% in non-ICU patients, features similar to 4.2% incidence found in the second wave in our study [10,[17][18][19].…”
Section: Discussionsupporting
confidence: 85%
“…It is also unclear why there are also thromboembolic events even with anticoagulation therapy. 6 Some studies showed that angiotensin II stimulates tissue factor expression in endothelial cells, causing the release of plasminogen-activator inhibitors from adipocytes. This mechanism leads to increased coagulation and impaired fibrinolysis, which may still be active after infection resolution.…”
Section: Discussionmentioning
confidence: 99%
“…PE is the most common thrombotic complication, 6,22 presenting on average 23 days after symptom onset. 7 found that PE had the highest incidence among recovered COVID-19 patients with thromboembolic outcomes, with obese patients especially susceptible to this condition.…”
Section: Discussionmentioning
confidence: 99%